The 'Little Ice Age' in the Southern Hemisphere in the context of the last 3000 years: Peat-based proxy-climate data from Tierra del Fuego. (December 2014) - Chambers, Frank M; Brain, Sally A; Mauquoy, Dmitri; McCarroll, Julia; Daley, Tim
The so-called 'Little Ice Age' (LIA) of the 15th to 19th centuriesad is well-attested from much of Europe and from some other parts of the Northern Hemisphere. It has been attributed to solar forcing, associated with reduced solar activity, notably during the Spörer, Maunder and Dalton solar minima, although other causes have also been proposed and feature strongly in recent papers. Detection of the LIA in some proxy-climate records from the Southern Hemisphere is less clear, leading to suggestions that the LIA was perhaps not a global phenomenon. Resolving this issue requires more data from the Southern Hemisphere. We present proxy-climate data (plant macrofossils; peat humification) covering the past three millennia from an ombrotrophic mire (peat bog) in Tierra del Fuego, southern South America, but focus our discussion on the period traditionally associated with the LIA. During parts of this time, the mire surface was apparently relatively dry compared with much of its 3000-year record. It was reported earlier that a particularly dry episode in the mire coincided with the 2800 cal. BP 'solar' event (since identified as a Grand Solar Minimum), which was attributed to solar-driven changes in atmospheric circulation, and more specifically to a shift in position of the Westerlies. Parts of the LIA record show a similar shift to dryness, and we invoke a similar cause. The shifts to and from dry episodes are abrupt. These new data support the concept of a global LIA, and for at least the intense dry episodes might reinforce the claim for solar forcing of parts of the LIA climate.